The Expression and Significance of Interleukin-9, Interleukin-6 and Tumor Necrosis Factor-α in Colonic Mucosa of Patients with Ulcerative Colitis - Dong-dong QU (Journal of International Translational Medicine, 2016)
Objective: To investigate the expression and significance of interleukin (IL)-9, IL-6 and tumor necrosis factor-α (TNF-α) in colonic mucosa of patients with ulcerative colitis (UC).Methods: The expression levels of IL-9, IL-6 and TNF-α in colonic mucosa were detected by immunohistochemistry in 60 patients with UC (38 with mild UC and 22 with moderate-severe UC), and in 20 controls. To explore whether there were some influence from the age and gender, we further divided these 60 patients into <20 years group, 20-49 years group, and >49 years.Results: The percentage of positive cells of IL-9 in colonic mucosa of moderate-severe UC group was significantly higher than that in mild UC group (P<0.05), IL-9 of mild group was higher than that of control group (P<0.01), and the expression levels of IL-6 and TNF-α had the same tendency as that of IL-9. For UC patients, the percentage of IL-9 positive cells in 20-49 years old group (85.0%) was higher than that in ≤20 years group (0.0%) or ≥49 years group (58.8%), and significant differences were shown. The percentage of the TNF-α positive cells in moderate-severe UC group (81.8%) was higher than that in mild UC group (51.3%) (P<0.05), which was also evidently higher in mild group than that in control group (5.0%) (P<0.01). The percentage of TNF-α positive cells in 20-49 years UC group (75.0%) was higher than that in <20 years UC group (67.6%), and the difference was statistically significant. There was no significant difference in the percentage of IL-9, IL-6, and TNF-α positive cells between females (75.0%) and males (72.7%) (P>0.05).Conclusion: The expression levels of IL-9, IL-6 and TNF-α in colonic mucosa of UC are higher than those in the controls, and are all related to the severity of UC. It is speculated that IL-9, IL-6 and TNF-α play important roles in UC occurrence and development.